The Reporting of COVID-19 In International Media (International Journal of Innovative Research in Engineering & Management, 2021)
On Dec. 1, 2019, the initial COVID-19 cases were documented,  with the cause being a then-new coronavirus called as severe  acute respiratory illness coronavirus 2. (SARS-CoV-2). SARS CoV-2 may have begun in animals and advanced into a human infectious illness. Virus that evolved in eagles, pigs, dogs, and  various Animals have developed in the previous to be deadly to  people, resulting in several outbreaks of infectious illness. The  novel coronavirus 2019 (COVID-19) has been recognized the  World Health Organization has confirmed it a universal community fitness emergency. Since, the epidemic has  dominated the front pages of major worldwide news outlets that  convey information to the world's inhabitants. However, owing  to the epidemic being dubbed "Chinese viral pandemonium,"  some media reporting of COVID-19 has had a severe impact  on Chinese travelers' mental health. President Donald Trump,  for example, referred to COVID-19 as the "Chinese virus" in a  tweet. Violent assaults against Chinese overseas travelers and  students have occurred from this discriminatory labeling.  During the worldwide COVID-19 outbreak, this viewpoint  piece examines how false and discriminating media stories may  impair the mental health of ethnically Chinese travelers. The  future scope of this study is that media is the cheapest and fast  way of spreading information.
Keywords: Coronavirus; Epidemic; Health; Media; News